2018
DOI: 10.1038/s41419-018-0771-y
|View full text |Cite
|
Sign up to set email alerts
|

The novel long noncoding RNA u50535 promotes colorectal cancer growth and metastasis by regulating CCL20

Abstract: Long noncoding RNAs (lncRNAs) have been emerging as master regulators of tumor growth and metastasis, but the functions and underlying mechanisms of lncRNAs in colorectal cancer (CRC) still need to be clarified. Here, we found a novel lncRNA u50535, which was greatly overexpressed in CRC tissues and was associated with poor prognosis in CRC patients. Function studies showed that u50535 was an oncogene in CRC both in vitro and in vivo. In mechanism, through RNA sequencing and rescue assay, we found that u50535 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…Wei et al (14) revealed that lncRNA activated by TGFβ (ATB) was highly expressed in lung cancer tissues, which was closely associated with tumor size and metastasis, and inhibition of lncRNA ATB significantly repressed lung cancer cell proliferation and migration. Yu et al (15) recently found that lncRNA-u50535 was overexpressed in colorectal cancer (CRC) tissues, and its high expression was associated with poor prognosis of CRC patients. In addition, they also demonstrated that lncRNA-u50535 increased CRC cell growth by upregulating CCL20 expression (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wei et al (14) revealed that lncRNA activated by TGFβ (ATB) was highly expressed in lung cancer tissues, which was closely associated with tumor size and metastasis, and inhibition of lncRNA ATB significantly repressed lung cancer cell proliferation and migration. Yu et al (15) recently found that lncRNA-u50535 was overexpressed in colorectal cancer (CRC) tissues, and its high expression was associated with poor prognosis of CRC patients. In addition, they also demonstrated that lncRNA-u50535 increased CRC cell growth by upregulating CCL20 expression (15).…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al (15) recently found that lncRNA-u50535 was overexpressed in colorectal cancer (CRC) tissues, and its high expression was associated with poor prognosis of CRC patients. In addition, they also demonstrated that lncRNA-u50535 increased CRC cell growth by upregulating CCL20 expression (15). However, the function of lncRNA-u50535 and whether it could regulate CCL20-related signaling in lung cancer progression remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Also, CCL20 is highly expressed in colorectal cancer cells and contributes to cancer progression 23,24 . For example, in CRC, Yu X et al and Cheng et al demonstrated that CCL20 overexpression could promote cell proliferation and migration in CRC 25 . Additionally, Wang D et al reported that the high level of CCL20 was closely associated with the poor survival of CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that CVB-D may suppress EMT by regulating the expression of Snail. RNA-seq techniques have been used for the study of numerous diseases, such as bladder, gastric, liver, cervical, colon and breast cancers (45)(46)(47)(48)(49)(50). RNA-seq is an effective tool for sequencing transcripts using high-throughput sequencing technology.…”
Section: Discussionmentioning
confidence: 99%